Cost Efficiency of Finnish Municipalities in Basic Service Provision 1994-2002 - Heikki A. Loikkanen; Ilkka Susiluoto (European Regional Science Association (ERSA), 2005)
Cost efficiency of basic welfare service provision in 353 Finnish municipalities in 1994-2002 is investigated. In a basically two tier public sector (central government and municipalities) the municipal sector has a central role in the Finnish economy as a provider of welfare services. Data Envelopment Analysis (DEA), a non-parametric linear programming method is employed, calculating a best practise total cost frontier for the decision making units, and comparing the various DMUs with this frontier. The outputs consist of up to ten volume indicators of services in health, social and educational sector. As the combined input, total real production costs of these services is used. According to the results efficiency differences were considerable between the municipalities, and a small group of a peripheral municipalities scored clearly below the others. Also annual changes in cost efficiency were estimated. As a second stage, differences in the DEA cost efficiency scores were explained with statistical models. Here the explanatory variables included structural and demographic indicators of municipalities, their location and measures of political power at local level. According to the results several of these variables had an expected effect on cost efficiency.
Keywords: 330